Hematopoietic stem cells from pluripotent stem cells: Clinical potential, challenges, and future perspectives. (29th July 2020) - Demirci, Selami; Leonard, Alexis; Tisdale, John F.
Abstract: The generation of hematopoietic stem cells (HSCs) from induced pluripotent stem cells (iPSCs) is an active and promising area of research; however, generating engraftable HSCs remains a major obstacle. Ex vivo HSC derivation from renewable sources such as iPSCs offers an experimental tool for studying developmental hematopoiesis, disease modeling, and drug discovery, and yields tremendous therapeutic potential for malignant and nonmalignant hematological disorders. Although initial attempts mostly recapitulated yolk sac primitive/definitive hematopoiesis with inability to engraft, recent advances suggest the feasibility of engraftable HSC derivation from iPSCs utilizing ectopic transcription factor expression. Strategic development for de novo HSC generation includes further investigations of HSC ontogeny, and elucidation of critical signaling pathways, epigenetic modulations, HSC and iPSC microenvironment, and cell-cell interactions that contribute to stem cell biology and function. : Abstract : A potential future clinical setting for patient-specific hematopoietic stem cell (HSC) or blood product generation from induced pluripotent stem cells (iPSCs).